2021
DOI: 10.4236/ojped.2021.113047
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcome of Overt Stroke in Sickle Cell Patients Admitted in Two Reference Hospitals in Yaounde and Douala

Abstract: Background: Worldwide, the prevalence of sickle cell disease (SCD) as of 2016 was estimated at 2%; that is 300,000 births annually. This study was focused on homozygous sickle cell disease which leads to several complications notably hemolytic crises, aplastic crises and vaso-occlusive crises like stroke. Sickle cell disease is the most common cause of childhood stroke. Stroke occurs in 17% -24% of sickle cell children worldwide. Objectives: To determine the risk factors for overt stroke and outcome at dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Mwangala et al [ 49 ] also reported that caregiver's age and secondary level of education negatively influence the QoL of caregivers, while Van den tweel [ 9 ] additionally reported that limitation in daily activities and vitality negatively influenced QoL. SCD is a chronic disease, which may lead to debilitating complications like stroke [ 3 , 51 , 52 ] and femoral osteonecrosis [ 53 , 54 ] which could significantly impair patient's mobility and autonomy making them fully dependent on caregivers. In addition, the intensity of pain crises may cause insomnia and psychological distress in caregivers, which may affect their quality of life [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mwangala et al [ 49 ] also reported that caregiver's age and secondary level of education negatively influence the QoL of caregivers, while Van den tweel [ 9 ] additionally reported that limitation in daily activities and vitality negatively influenced QoL. SCD is a chronic disease, which may lead to debilitating complications like stroke [ 3 , 51 , 52 ] and femoral osteonecrosis [ 53 , 54 ] which could significantly impair patient's mobility and autonomy making them fully dependent on caregivers. In addition, the intensity of pain crises may cause insomnia and psychological distress in caregivers, which may affect their quality of life [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sickle cell disease (SCD) is one of the most common genetic blood disorders [1]. It manifests clinically as painful vasoocclusive crises and chronic haemolytic anemia with episodes of acute worsening and bacterial infections, causing heavy morbidity and mortality in countries with limited resources [2][3][4]. According to available evidence, Nigeria is believed to have the highest number of individuals afected by sickle cell disease on a global scale [5].…”
Section: Introductionmentioning
confidence: 99%